2007
DOI: 10.1159/000110453
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Silibinin Decreases Glucose-6-Phosphate Hydrolysis in Perifused Rat Hepatocytes by an Inhibitory Effect on Glucose-6-Phosphatase

Abstract: Background/Aims: The flavonoid silibinin has been reported to be beneficial in several hepatic disorders. Recent evidence also suggests that silibinin could be beneficial in the treatment of type 2 diabetes, owing to its anti-hyperglycemic properties. However, the mechanism(s) underlying these metabolic effects remains unknown. Methods: The effects of silibinin on liver gluconeogenesis were studied by titrating hepatocytes from starved rats with sub-saturating concentrations of various exogenous substrates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 38 publications
4
44
0
11
Order By: Relevance
“…The mechanism of action of silymarin may have an effect on the kinetics of glucose-6 phosphatase and inhibition of gluconeogenesis, increase insulin and improve pancreatic function, in addition to reducing hydroxy-3-methylglutaryl-CoA reductase and improving liver function. Silymarin acts by inhibiting hepatic glucose-6-phosphatase hydrolysis in perfused rat hepatocytes by an inhibitory effect on glucose-6-phosphatase and gluconeogenesis (Guigas et al, 2007). Silymarin recovers pancreatic function to increase insulin level.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of silymarin may have an effect on the kinetics of glucose-6 phosphatase and inhibition of gluconeogenesis, increase insulin and improve pancreatic function, in addition to reducing hydroxy-3-methylglutaryl-CoA reductase and improving liver function. Silymarin acts by inhibiting hepatic glucose-6-phosphatase hydrolysis in perfused rat hepatocytes by an inhibitory effect on glucose-6-phosphatase and gluconeogenesis (Guigas et al, 2007). Silymarin recovers pancreatic function to increase insulin level.…”
Section: Discussionmentioning
confidence: 99%
“…Silibinin, a flavonoid isolated from milk thistle (Silybum marianum) and has been used clinically for thousands of years in China and Europe as an anti-hepatotoxic agent to treat liver diseases, especially alcoholic liver disease (Brandon-Warner et al, 2010; Guigas et al, 2007). Recent studies have shown that silibinin has a strong antioxidant activity, increases cellular glutathione content, induces superoxide dismutase (SOD), antagonizes manganese-induced neurotoxicity in adult mice, and inhibits lipid peroxidation (Schumann et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, silibin inhibits gluconeogenesis in perifused hepatocytes independently of the gluconeogenic substrate. Furthermore, silibin inhibits glucose-6-phosphate hydrolysis in a variable manner, independently of the carbohydrate source, but it does not seem to have significant effects in the fructose cycle [7].…”
Section: In Vitro Studiesmentioning
confidence: 94%